Maternal mortality: scenario, causes and prevention of the tragedy in Indian context with special consideration to Assam, India - Ahmed, Sultana Jesmin; Siddique, Mir Alam; Sultana, Nasima (International Journal Of Community Medicine And Public Health, 2017)
Though child birth gives joy to mother and family, yet this joy may transform to tragedy in the event of maternal death. Maternal mortality has been identified as a priority on health policy and research agendas for developing countries. MMR has been decreased from 398/100,000 live births in 1997 to 178 in 2013 India and 347 in 2011 to 301 in 2013 in Assam, India. Maternal death may occur during antenatal, intranatal or postnatal period thus necessitating services during these periods. For pregnant women during antenatal, intranatal or postpartum period – ante natal care services, institutional delivery, access to basic emergency obstetric care (BEmOC) and comprehensive emergency obstetric care ( CEmOC), post natal care, referral services should be provided. In the event of injection oxytocin not being available due to constraints of optimal storage conditions or other logistical barriers, misoprostol is recommended to be given for prevention of PPH. Government of India policies and strategies (NPP/RCH II) have focused on enhancing-access and availability of comprehensive abortion care services in both the public and private sector. Maternal death review should be done in case of any maternal death to find out the associated factors. “Maternal near miss” surveillance is an effective tool for improving safe motherhood programs. Government of Assam has kept goal 2 under Assam bikas yojna: reduction in maternal mortality ratio to 210 per 100000 live births. Some planned strategy taken for achieving this goal. But for success in reducing maternal death the community will need to be involved not only through educating them about the signs and symptoms of emergency but also to develop appropriate mechanisms for ensuring that women in distress get the quality care.